2018
DOI: 10.1101/325407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supragingival plaque microbiome ecology and functional potential in the context of health and disease

Abstract: To address the question of how microbial diversity and function in the oral cavities of children relates to caries diagnosis, we surveyed the supragingival plaque biofilm microbiome in 44 juvenile twin pairs. Using shotgun sequencing, we constructed a genome encyclopedia describing the core supragingival plaque microbiome. Caries phenotypes contained statistically significant enrichments in specific genome abundances and distinct community composition 5 profiles including strain-level changes. Metabolic pathwa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 71 publications
(101 reference statements)
0
12
0
Order By: Relevance
“…This indicates that S. mutans, when present, has a large influence on the pathogenicity of the oral microbiome due to its prodigious capacity to generate insoluble glucans and resultant biofilms (9, 26). Other oral microbiome studies have found S. mutans at low abundances (20, 21, 54), and the use of saliva in this study may explain its rarity, and possibly underestimation, here—as an exceptional biofilm-former, it is less likely to be shed from its dental plaque residence into the salivary milieu (55).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This indicates that S. mutans, when present, has a large influence on the pathogenicity of the oral microbiome due to its prodigious capacity to generate insoluble glucans and resultant biofilms (9, 26). Other oral microbiome studies have found S. mutans at low abundances (20, 21, 54), and the use of saliva in this study may explain its rarity, and possibly underestimation, here—as an exceptional biofilm-former, it is less likely to be shed from its dental plaque residence into the salivary milieu (55).…”
Section: Discussionmentioning
confidence: 60%
“…S. gordonii ), further illustrating a need for studies utilizing more in-depth sequencing and analysis methods (5). Although several shotgun metagenomic surveys of the oral microbiota have been performed (2023), they have not employed differential ranking techniques with consistent reference frames, as detailed in Morton et al 2019 (13).…”
Section: Introductionmentioning
confidence: 99%
“…For this, we combined our 43 MAGs with 9 human oral TM7 genomes from the literature. In addition to 3 single amplified genomes that we downloaded from the Integrated Microbial Genomes and Microbiomes database 285 (IMG/M) (Chen et al, 2019c) and refined (see Methods) and a MAG from Marcy et al (Marcy et al, 2007), we included 4 MAGs from Espinoza et al (Espinoza et al, 2018) after manually refining composite TM7 genomes (Shaiber & Eren, 2019), and the first cultivated strain of TM7, TM7x (He et al, 2015) ( Supplementary Table 7d). The phylogenomic analysis of these 52 genomes separated tongue and plaque-associated 290 genomes into distinct branches, where we could identify a single node on the tree that separated 41 of the 42 plaque associated genomes, suggesting that the site-specificity of TM7 is an ancestral trait.…”
Section: Tm7 Phylogenomic Clades Correspond To Site Of Recoverymentioning
confidence: 99%
“…Additional recent cultivation efforts are proving 120 successful in providing access to a wider variety of oral TM7 Cross et al, 2019). Recent genomeresolved and single-amplified genomics studies have also produced genomes for oral GN02 and SR1 (Campbell et al, 2013;Espinoza et al, 2018), and recently the first targeted isolation of oral SR1 strains has been reported, but genomes were not produced 125 . Despite the promise of these studies, our understanding of the ecology and evolution of these fastidious oral clades is incomplete.…”
Section: Introduction 50mentioning
confidence: 99%
“…These results suggest that biofilm α ( Figure 1) may be associated with an increase in the abundance of biofilm formers, while biofilms β1 and β2 ( Figure 1) may be associated with a reduction in the number of biofilm formers. In agreement with this idea, the bacterial genera with higher abundance in response to anti-tick immunity include the strong biofilm formers Mycobacterium (33), Tepidimonas (34), Rothia (35) and Leuconostoc (36), whereas A. phagocytophilum infection and antimicrobial peptide reduced the presence of the biofilm formers Gracilibacteria (37) and Enterococcus (3), respectively.…”
Section: Effect Of Biological Disturbance On Taxonomic and Functionalmentioning
confidence: 69%